Examining The Link Between Competence and Motivation on Urban Farmers' Performance: The Mediating Role of Job Satisfaction - Kuleh, Yohanes; Darma, Dio Caisar; Pujiastuti, Yunita Ali; Nurhikmat, Muhammad; Sampeliling, Alexander; Purwaningsih, Fita; Ashari, Ihsan (Indonesian Journal of Social Science Research, 2025)
The relocation of Indonesia’s Capital City/Ibu Kota Nusantara (IKN), from Jakarta to East Kalimantan began in 2022, with the government citing economic equity as the primary rationale. Economic development cannot progress without revitalization across all sectors. Agriculture is a sector with significant development potential, despite its current suboptimal operations. Among agricultural activities, oil palm plantations are one of the most prominent and important contributors. Effective human resource management (HRM) of farmers is crucial to driving agricultural economic growth. This study aims to examine the causal relationship between competence and motivation on farmer performance, with job satisfaction as a mediating variable. The sample comprises 138 urban farmers who are members of the Farmers' Group Association (GAPOKTAN) engaged in palm oil production. Data were collected in Sukaraja Village, Penajam Paser Utara (PPU) Regency. The approach was conducted using path analysis. Empirical results indicate that both competence and motivation significantly affect job satisfaction and performance. Additionally, job satisfaction is significantly related to performance. Thus, competence and motivation influence performance indirectly through job satisfaction. This study offers practical benefits for decision-makers, particularly GAPOKTAN, by emphasizing the importance of enhancing farmer competence. The findings also encourage further investigation into additional aspects that may affect farmer performance.